Intermediate role of gut microbiota in vitamin B nutrition and its influences on human health - Wan, Zhijie; Zheng, Jianheng; Zhu, Zhigang; Sang, Lan; Zhu, Jinwei; Luo, Shizheng; Zhao, Yixin; Wang, Ruirui; Zhang, Yicui; Hao, Kun; Chen, Liang; Du, Jun; et al. (Frontiers in Nutrition, 2022)
Vitamin B consists of a group of water-soluble micronutrients that are mainly derived from the daily diet. They serve as cofactors, mediating multiple metabolic pathways in humans. As an integrated part of human health, gut microbiota could produce, consume, and even compete for vitamin B with the host. The interplay between gut microbiota and the host might be a crucial factor affecting the absorbing processes of vitamin B. On the other hand, vitamin B supplementation or deficiency might impact the growth of specific bacteria, resulting in changes in the composition and function of gut microbiota. Together, the interplay between vitamin B and gut microbiota might systemically contribute to human health. In this review, we summarized the interactions between vitamin B and gut microbiota and tried to reveal the underlying mechanism so that we can have a better understanding of its role in human health.